2008
DOI: 10.1021/jp8015694
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Symmetry and Reorientation Dynamics of Perylenes in Liquid Solutions: Time-Resolved Fluorescence Depolarization Studies Using One- and Two-Photon Excitation

Abstract: The excited-state symmetry and molecular reorientation of perylene, 1,7-diazaperylene, and 2,5,8,11-tetra- tert-butylperylene have been studied by different fluorescence depolarization experiments. The first excited electronic singlet state was reached through one-photon excitation (OPE) and two-photon excitation (TPE). A 400 and 800 nm femtosecond laser pulse was used for this purpose, and data were collected by means of the time-correlated single-photon counting technique. It is found that the rotational cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
(123 reference statements)
0
24
0
Order By: Relevance
“…Transforming from the laboratory to molecular frame of reference and performing the necessary orientational averaging is most conveniently achieved using a spherical tensor formalism. 22,2427 With this approach and assuming a planar transition, valid for NAD(P)H, 2 Ω can be written as…”
Section: Introductionmentioning
confidence: 99%
“…Transforming from the laboratory to molecular frame of reference and performing the necessary orientational averaging is most conveniently achieved using a spherical tensor formalism. 22,2427 With this approach and assuming a planar transition, valid for NAD(P)H, 2 Ω can be written as…”
Section: Introductionmentioning
confidence: 99%
“…The planar heteroaromatic molecules are densely packed ( cryst = 1.42 Mg•m -3 ) forming a modified herringbone structure. Radical anions and radical cations of 1 were also studied 11 as special aspects of the aromaticity 12 and dynamics in solution 13,14 and even special aspects concerning the electronic excitation. 15,16 1,7-Diazaperylene (1) is accessible on a lab scale in a five step synthesis from 1,5-diaminoanthraquinone and the Meerwein reaction 17,18 with vinylidene chloride; however, the upscaling necessary for its use in a functional material capacity is limited by both the low solubility of intermediates and the need to use a considerable amount of additional Raney nickel as a reducing agent.…”
mentioning
confidence: 99%
“…31 Only in some cases, two rotational correlation times can be resolved in oblate molecules. 16 In this study, a two-exponential decay law was used for analysis of the polarized fluorescence signals in Eqs. (1) and (2), and it was found that it perfectly fitted the experimental data.…”
Section: Experimental Arrangementmentioning
confidence: 99%
“…The use of femtosecond laser pulses in TPEF experiments makes it possible to track the evolution of the fluorescence from the anisotropic ensembles of excited molecules in the real time domain with high temporal resolution. 8,16 The Braunschweig group 8,9,17,18 has recently used the femtosecond 2C2P excitation scheme for detailed investigation of important UV fluorophores: p-terphenyl (PTP) 17 and 2-methyl-5-t-butylp-quaterphenyl (DMQ). 18 The complete set of molecular parameters has been determined from experiment in those studies which met the conditions of the complete polarization experiment.…”
Section: Introductionmentioning
confidence: 99%